Inestigating The Role of Organizational Culture and Knowledge Sharing on Teacher Innovation Capability - Asbari, Masduki (AGUSPATI RESEARCH INSTITUTA, 2024)
This study aims to measure the influence of organizational culture on teacher innovation capability in Indonesia mediated by tacit and explicit knowledge sharing. Data collection was carried out by simple random sampling via electronic to a population of teachers in Banten The returned and valid questionnaire results were 800 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are organizational culture has a positive and significant effect on teacher innovation capability, both directly and through mediating tacit knowledge sharing. Organizational culture has a positive and significant effect on explicit knowledge sharing. While explicit knowledge sharing has not significant effect on teacher innovation capability. This novel research is proposing a model to build teacher innovation capability among teachers through organizational culture with tacit & explicit knowledge sharing as mediation. This research can pave the way to improve teacher readiness in facing the era of education 4.0.